Agriculture and international trade : law, policy, and the WTO - Cardwell, Michael; Grossman, Margaret R.; Rodgers, C. P. (Christopher P.) (CABI Pub., 2003)
This book addresses the interface between the law of international trade as it relates to agriculture, the emerging legal and economic order for agricultural trade under the auspices of the World Trade Organization (WTO), and their impact on agricultural policy reform in the EU and the USA. The book's particular focus is on key issues emerging in the Millennium Round of WTO negotiations, leading up to 2005 and the conclusion of new WTO agreements on agriculture and associated matters. The book has 12 chapters and a subject index.